2013
DOI: 10.5539/ass.v9n4p84
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender and Attitude of Pre-Service Teachers towards On-Line Instruction in a Selected University in South-western Nigeria

Abstract: The study examined the influence of gender and attitude of pre-service teachers on habitual use of online instruction in Faculty of Education at Obafemi Awolowo University, Ile Ife, Nigeria. The sample size of 300 part two Education students (150 males and 150 females) was used as sample for the study. Data were collected using 12 items structured questionnaire. The reliability of the questionnaire was determined using Cronbach Alpha and a reliability coefficient of 0.86 was obtained. The results showed that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The primary instrument for data collection in this study was semi-structured focus group interviews. These interviews were guided by a set of predetermined questions, which were derived from existing literature (Fishbein & Ajzen, 1975;Johns & Saks, 2011;Lateef & Alaba, 2013;Theng, 2009;Venkatesh & Davis, 2000). The questions were designed to explore participants' perceptions and experiences with MALL.…”
Section: Tools and Instrumentsmentioning
confidence: 99%
“…The primary instrument for data collection in this study was semi-structured focus group interviews. These interviews were guided by a set of predetermined questions, which were derived from existing literature (Fishbein & Ajzen, 1975;Johns & Saks, 2011;Lateef & Alaba, 2013;Theng, 2009;Venkatesh & Davis, 2000). The questions were designed to explore participants' perceptions and experiences with MALL.…”
Section: Tools and Instrumentsmentioning
confidence: 99%
“…This body of literature suggests that teachers who perceive the system as useful and easy to use develop better attitudes towards online teaching, and self-efficacy and belief link to attitude formation (Bubou and Job, 2020). Teachers who have technology and communication self-efficacy, are more likely to have positive attitudes towards online teaching (Yildiz Durak, 2018), in which male teachers' readiness for online teaching is higher than their female counterparts (Bubou and Job, 2020); however, Lateef and Alaba (2013) found the opposite and Adebowale et al (2010) found no relationship. UAE students believed that the value of an online course management system would benefit them as equal as a blackboard in studies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Education, a fundamental pillar of personal development, continually evolves in response to technological advancements throughout an individual's lifespan (Sungur & Ateş, 2023;Jovanova-Mitkovska, 2010;Ghavifekr & Rosdy, 2015;Raja & Nagasubramani, 2018;Dos Santos, 2024). The pervasive influence of the internet globally has radically reshaped education, bolstering pedagogical efficacy through the seamless integration of technology (Lateef & Alaba, 2013). That is, the internet has significantly transformed education, enhancing teaching efficiency through technological integration.…”
Section: Introductionmentioning
confidence: 99%